ELECTORAL SYSTEMS AND THE DEVELOPMENT OF THE EU MEMBER STATES: AN EMPIRICAL EVIDENCE - D. Pastarmadzhieva (Trakia Journal of Sciences)
The electoral system plays a significant role in various areas of the functioning of the states. Alongside this, there are areas, which can't be affected by the change in the electoral system or of the electoral system type. However, in Bulgaria, there is a debate on the introduction of the majority/plurality electoral system and one of the arguments is related to the possible overall positive effect on the functioning of the country. Thus, the purpose of the current study is to identify if the electoral system is relevant for the development of the EU member states. The object of the study is the countries, members of the European Union, studied in 2018. Focus of the research is their electoral system and their development, measured on a number of indicators. For the purposes of the analysis statistical methods (frequencies and cross tables) and comparative approach are used. The results show that the type of electoral system is not relevant for the development of EU member states, measured on the selected indicators.